HETERONORMATIVITY IN MS. MARVEL COMICS - Muhammad, Guntur Aghni; Yatmikasari, Ika (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
The main subject of this study is the implementation of traditional masculinity and femininity theories within the Heteronormativity framework in 3 sequential volumes of Ms. Marvel by author G. Willow Wilson. The author relies on a post-structuralist feminist framework to describe gender stereotypes, using content analysis methods, which are mixed-methods quantitatively and qualitatively. This thesis attempts to answer a fundamental question; How Gender Stereotypes were presented in Ms. Marvel Comics?. In this findings, the data that have been collected shows significant differences in the distribution of social role attributes, traits, behaviors in characters divided into categories of masculine and feminine attributes. These quantitative data are then processed. Masculine attributes still dominated by male characters, and vice versa. , Nevertheless, there were at least a total of 67% (n=4) of female characters who were more associated with masculine attributes.